Properdin inhibition ameliorates hepatic ischemia/reperfusion injury without interfering with liver regeneration in mice - Kusakabe, Jiro; Hata, Koichiro; Tajima, Tetsuya; Miyauchi, Hidetaka; Zhao, Xiangdong; Kageyama, Shoichi; Tsuruyama, Tatsuaki; Hatano, Etsuro (Frontiers in Immunology, 2023)
Hepatic ischemia/reperfusion injury (IRI) often causes serious complications in liver surgeries, including transplantation. Complement activation seems to be involved in hepatic IRI; however, no complement-targeted intervention has been clinically applied. We investigated the therapeutic potential of Properdin-targeted complement regulation in hepatic IRI. Male wild-type mice (B10D2/nSn) were exposed to 90-minute partial hepatic IRI to the left and median lobes with either monoclonal anti-Properdin-antibody (Ab) or control-immunoglobulin (IgG) administration. Since the complement system is closely involved in liver regeneration, the influence of anti-Properdin-Ab on liver regeneration was also evaluated in a mouse model of 70% partial hepatectomy. Anti-Properdin-Ab significantly reduced serum transaminases and histopathological damages at 2 and 6 hours after reperfusion (P <0.001, respectively). These improvements at 2 hours was accompanied by significant reductions in CD41+ platelet aggregation (P =0.010) and ssDNA+ cells (P <0.001), indicating significant amelioration in hepatic microcirculation and apoptosis, respectively. Characteristically, F4/80+ cells representing macrophages, mainly Kupffer cells, were maintained by anti-Properdin-Ab (P <0.001). Western blot showed decreased phosphorylation of only Erk1/2 among MAPKs (P =0.004). After 6 hours of reperfusion, anti-Properdin-Ab significantly attenuated the release of HMGB-1, which provokes the release of proinflammatory cytokines/chemokines (P =0.002). Infiltration of CD11b+ and Ly6-G+ cells, representing infiltrating macrophages and neutrophils, respectively, were significantly alleviated by anti-Properdin-Ab (both P <0.001). Notably, anti-Properdin-Ab did not affect remnant liver weight and BrdU+ cells at 48 hours after 70% partial hepatectomy (P =0.13 and 0.31, respectively). In conclusion, Properdin inhibition significantly ameliorates hepatic IRI without interfering with liver regeneration.